2000
DOI: 10.1073/pnas.97.7.3422
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation ofex vivoexpanded endothelial progenitor cells for therapeutic neovascularization

Abstract: Animal studies and preliminary results in humans suggest that lower extremity and myocardial ischemia can be attenuated by treatment with angiogenic cytokines. The resident population of endothelial cells that is competent to respond to an available level of angiogenic growth factors, however, may potentially limit the extent to which cytokine supplementation enhances tissue neovascularization. Accordingly, we transplanted human endothelial progenitor cells (hEPCs) to athymic nude mice with hindlimb ischemia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
993
4
30

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,587 publications
(1,056 citation statements)
references
References 38 publications
29
993
4
30
Order By: Relevance
“…4,5 Ex vivo cultivated EPCs derived from mononuclear cells of human peripheral blood or cord blood have been successfully shown to incorporate into neovasculature and contribute to functional recovery of ischemic tissue. 6,7 In this study, we examined whether EPCs could promote tumor angiogenesis and found that the tumor growth was enhanced by the administration of EPCs. It is suggested that accumulated EPCs differentiated to tumor vasculature, increased the tumor blood supply, and thereby increased the tumor volume.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Ex vivo cultivated EPCs derived from mononuclear cells of human peripheral blood or cord blood have been successfully shown to incorporate into neovasculature and contribute to functional recovery of ischemic tissue. 6,7 In this study, we examined whether EPCs could promote tumor angiogenesis and found that the tumor growth was enhanced by the administration of EPCs. It is suggested that accumulated EPCs differentiated to tumor vasculature, increased the tumor blood supply, and thereby increased the tumor volume.…”
Section: Discussionmentioning
confidence: 99%
“…The beauty of this system is that the in vivo potential of the injected cells can be investigated [reviewed in (48,49)]. Using this system, in the year 2000, Kalka et al were able to demonstrate by histological assessment that injected EPCs incorporate into sites of neovascularization (50). Other than in ischemic tissue and very rarely in the spleen, EPCs were detected neither in other organs nor in the contralateral nonischemic hindlimb.…”
Section: Functional Analysismentioning
confidence: 99%
“…Therefore, the field of cell-based therapy has expanded also in patients with PAOD. Kalka et al (50) administered ex vivo expanded human EPCs to athymic nude mice with HLI. Histological evidence of the cell incorporation into sites of neovascularization was associated with an increase in capillary density and an enhancement of limb blood flow recovery in mice receiving human EPCs.…”
Section: Peripheral Arterial Occlusive Diseasementioning
confidence: 99%
“…By contrast, other studies have shown that stem cells residing in one tissue can differentiate into cell types of another tissue. For example, reserve stem cells derived from bone marrow can differentiate into neurons and glia (Eglitis and Mezey, 1997;Kopen et al, 1999), restore dystrophin expression in skeletal muscle (Gussoni et al, 1999), serve as a source of hepatic oval cells (Petersen et al, 1999), provide cells for neovascularization (Asahara et al, 1999;Kalka et al, 2000), and restore cartilage, bone, and fat (Pittenger et al, 1999;Prokop, 1997;Yoo et al, 1998). Conversely, stem cells derived from neural tissues (Bjornson et al, 1999) and muscle tissues (Jackson et al, 1999) can differentiate into blood.…”
mentioning
confidence: 99%